Interference and Freedom: Conversations with Connections Artists - Simonsen, Barbara; Gade Nielsen, Elisabeth (Peripeti, 2022)
This is a collection of interviews with selected artists from the Connections residency programme (2017-2020), held, transcribed and edited by Barbara Simonsen and Elisabeth Gade Nielsen. The interviews revolve around artistic process, collaboration and creative freedom, and provide insight into how the framework of the residency (and its underlying concept of interference as a dramaturgical tool) feeds into the creative process.